2005
DOI: 10.1002/app.21854
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy‐silica nanocomposites: Preparation, experimental characterization, and modeling

Abstract: ABSTRACT:Silica nanoparticles having different sizes were obtained by the sol-gel process and characterized. The prepared nanoparticles were subsequently used as reinforcing fillers to prepare epoxy-based composites with a silica content ranging from 1 to 5 wt %. SEM analysis and tensile tests carried out on the silica-epoxy nanocomposites indicated the absence of particle aggregation and a reinforcing effect in terms of increased elastic modulus. Mechanical properties were also modeled by using a finite eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 33 publications
(23 reference statements)
5
46
0
3
Order By: Relevance
“…Pure nanoparticles at 2 wt% silica are well dispersed, achieving a large effective interface area; therefore, these provide stronger stiffening effects than those of micro-nanoparticles. Good dispersion of low-content silica nanoparticles was observed, which is in agreement with previous works by Bondioli et al [10], Zheng et al [9], and Feli and Jalilian [8]. This result suggests that composing silica micro and nanoparticles in appropriate ratios improves their dispersion up to certain weight fraction when using only a conventional mechanical mixer.…”
Section: Effects Of Silica Micro-nanoparticles On Dynamic Stiffnesssupporting
confidence: 91%
See 1 more Smart Citation
“…Pure nanoparticles at 2 wt% silica are well dispersed, achieving a large effective interface area; therefore, these provide stronger stiffening effects than those of micro-nanoparticles. Good dispersion of low-content silica nanoparticles was observed, which is in agreement with previous works by Bondioli et al [10], Zheng et al [9], and Feli and Jalilian [8]. This result suggests that composing silica micro and nanoparticles in appropriate ratios improves their dispersion up to certain weight fraction when using only a conventional mechanical mixer.…”
Section: Effects Of Silica Micro-nanoparticles On Dynamic Stiffnesssupporting
confidence: 91%
“…Welldispersed silica nanoparticles stiffen and toughen an epoxy adhesive more efficiently than silica microparticles owing to their larger surface-to-volume ratio, forming a more substantial matrix-filler interface area at a given weight fraction [1][2][3][4][5][6][7]. However, without any treatment, high-silica-content nanoparticles are difficult to disperse uniformly using a conventional mechanical mixer and tend to aggregate/agglomerate in the epoxy matrix [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental understanding is very limited in the field and often leads to the conclusion that approaches commonly used for particulate composites are not suitable when a nanometric phase is involved. [4] There have been significant efforts over the past decade to develop modified epoxies with various nano-additives including carbon nanotubes/fibres, exfoliated nanoclays, and organic/inorganic nanoparticles. However, few systems have achieved uniform dispersions of nanoparticles without agglomeration.…”
Section: Introductionmentioning
confidence: 99%
“…2. It is observed that for some nanocomposites, with the same filler volume fraction, the stiffness and strength increases as the particle size decreases [125,182,[224][225][226][227].…”
Section: Mechanical Property Enhancementmentioning
confidence: 99%